Role of premixed insulin analogues in the treatment of patients with type 2 diabetes mellitus: A narrative review (预混胰岛素类似物在2型糖尿病治疗中的作用：叙述性综述). (21st January 2014) - Elizarova, Svetlana; Galstyan, Gagik R.; Wolffenbuttel, Bruce H.R.
Abstract Because of the progressive nature of type 2 diabetes mellitus (T2DM), insulin therapy will eventually become necessary in most patients. Recent evidence suggests that maintaining optimal glycemic control by early insulin therapy can reduce the risk of microvascular and macrovascular complications in patients with T2DM. The present review focuses on relevant clinical evidence supporting the use of premixed insulin analogues in T2DM when intensifying therapy, and as starter insulins in insulin‐naïve patients. Our aim is to provide relevant facts and clinical evidence useful in the decision‐making process of treatment selection and individualized treatment goal setting to obtain sustained blood glucose control.